Isolation and characterization of a molybdenum-reducing and phenolic- and catechol-degrading enterobacter sp. Strain saw-2 - Sabullah M.K.; Rahman M.F.; Ahmad S.A.; Sulaiman M.R.; Shukor M.S.; Gansau A.J.; Shamaan N.A.; Shukor M.Y. (Seameo Biotrop, 2024)
Indexed by Scopus